Kemampuan Literasi Digital Mahasiswa Dalam Memanfaatkan Aplikasi Screencastify Pada Pembuatan Konten Video Pembelajaran Sejarah Kebudayaan Islam - Darise, Gina Nurvina (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the digital literacy abilities pf students in utilizing the screencastify application for creating video content on the history of Islamic culture teaching. The research employs a descriptive method with a qualitative approach. The research subjects consist of 30 active students from the 3rd semester of the Islamic Elementary School Teacher Education Program at the Faculty of Tarbiyah and Teacher Education, IAIN Manado. Data was collected through survey techniques and interviews. The research findings reveal that the majority students prossess proficient skills in using the Screencastify application to create video content related to the history of Islamic culture teaching. This proficiency encompasses the information technology serving as the transmitter medium of communication, and commad over content that is suitable for presentation or transmission within the realm of digital literacy. Despite inherent strengths and weaknesses the Screencastfy application proves highly advantageous in enhancing students’ digital literacy skills.